'Where do we belong?' Identity and autochthony discourse among Rwandophones Congolese. Issue 1 (2nd January 2017) - Alida, Furaha Umutoni
Abstract: The question of the Congolese-speaking Kinyarwanda (Rwandophones) citizenship in the Democratic Republic of Congo has been the subject of debate and a source of conflict. The opposition against Rwandophones draws upon the autochthony discourse, linking identity and space in assertions of whom is to be considered the original inhabitant and a son of the soil. According to the popular discourse in the Congo in relation to the autochthony discourse, Rwandophones do not belong to the Congo. Today little is known about how Rwandophones themselves legitimise their belonging to the Congo. Based on original field data collected among Rwandophones in North Kivu and in Rwanda between July 2011 and February 2014, this article analyses the narratives in which Rwandophones speak about and legitimise their belonging to the Congo. The article demonstrates ambivalence in relation to the autochthony discourse: while Congolese Rwandophones on the one hand embrace it, referring to their connection with Congolese soil as a way of legitimising their right to citizenship, they also challenge this discourse by arguing that belonging to the nation state does not require being tied to the soil.